Real-time and contactless measurements of thermal discomfort based on human poses for energy efficient control of buildings. (September 2019) - Yang, Bin; Cheng, Xiaogang; Dai, Dengxin; Olofsson, Thomas; Li, Haibo; Meier, Alan
Abstract: Individual thermal discomfort perception gives important feedback signals for energy efficient control of building heating, ventilation and air conditioning systems. However, there is few effective method to measure thermal discomfort status of occupants in a real-time and contactless way. A novel method based on contactless measurements of human thermal discomfort status was presented. Images of occupant poses, which are related to thermoregulation mechanisms, were captured by a digital camera and the corresponding 2D coordinates were obtained. These poses were converted into skeletal configurations. An algorithm was developed to recognize different poses related to thermal discomfort, such as hugging oneself or wiping sweat off the brow. The algorithm could recognize twelve thermal discomfort related human poses. These poses were derived from a questionnaire survey of 369 human subjects. Some other human subjects participated in the validation experiments of the proposed method. All twelve thermal discomfort related poses can be recognized effectively. Graphical abstract: Image 1 Highlights: 12 human poses of thermal comfort were defined based on 369 questionnaires. A contactless measurement method for thermal comfort was proposed. 10 sub-algorithms were constructed for poses recognition of thermal comfort.